Microwave-assisted hydrothermal synthesis of Nd, N, and P tri-doped TiO2 from TiCl4 hydrolysis and synergetic mechanism for enhanced photoactivity under simulated sunlight irradiation. (December 2015) - Jiang, Hongquan; Liu, Yanduo; Zang, Shuying; Li, Jingshen; Wang, Haiyan
Abstract: A novel high-performance Nd, N, and P tri-doped anatase-TiO2 (NdNPTO) nano-photocatalyst was obtained from TiCl4 hydrolysis by a rapid and energy-saving microwave-assisted hydrothermal method. The effects of Nd, N, or/and P doping on the structural, electronic and optical properties of TiO2 were characterized by X-ray diffraction, transmission electron microscopy, N2 adsorption–desorption isotherm, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, electron paramagnetic resonance, UV–vis absorbance spectroscopy, and photoelectrochemical measurements. NdNPTO exhibited excellent photoactivity for the degradation of 4-chlorophenol (4-CP) under simulated sunlight irradiation, which was much superior to commercial P25 TiO2 . Scavenging experiments reveal that OH in the solution was main reactive species, and photogenerated electrons also played a minor role by finally transformed OH. Synergetic mechanism for the enhanced photoactivity of NdNPTO was discussed in detail. It presented good photocatalytic stability towards degradation of 4-CP under simulated sunlight irradiation, and was suitable to wide application for environment remediation.